No Right to Rest: Police Enforcement Patterns and Quality of Life Consequences of the Criminalization of Homelessness. Issue 1 (January 2019) - Robinson, Tony
Laws restricting the behaviors of homeless people in public places are proliferating. Proponents argue that such "quality of life" laws will encourage homeless people to move off the streets and into services, and thereby improve their quality of life. Critics argue that these laws target vulnerable individuals and show little evidence of improving the lives of homeless people. To inform this debate, this article reports data from two separate surveys of Colorado homeless residents regarding their experiences with quality of life policing, supplemented by a review of police data regarding contacts, ticketing, and arrests of homeless people. The data reveal that the oft-stated goal of improving the quality of life of homeless residents through "tough love" policing campaigns has not been met. Instead, most homeless residents report their lives have become more challenging, more stressful, and less safe following expansion of quality of life policing.